2007
DOI: 10.3748/wjg.v13.i2.299
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract (EGb 761) attenuates lung injury induced by intestinal ischemia/reperfusion in rats: Roles of oxidative stress and nitric oxide

Abstract: The results indicate that EGb 761 has a protective effect on lung injury induced by II/R, which may be related to its antioxidant property and suppressions of neutrophil accumulation and iNOS-induced NO generation. EGb 761 seems to be an effective therapeutic agent for critically ill patients with respiratory failure related to II/R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 31 publications
8
39
0
2
Order By: Relevance
“…We for the first time also found that dexamethasone treatment after ischemic insult enhanced the well-documented protective effect of IPO. Several previous investigations demonstrated elevated MPO activities in lung tissue after I/R injury clearly exhibiting the inflammatory response and the active role of MPO in this cascade (Ai et al, 2013;Liu et al, 2007b). Our findings were in parallel with the others: lung tissue MPO activities of the rats subjected to I/R were significantly higher.…”
Section: Discussionsupporting
confidence: 89%
“…We for the first time also found that dexamethasone treatment after ischemic insult enhanced the well-documented protective effect of IPO. Several previous investigations demonstrated elevated MPO activities in lung tissue after I/R injury clearly exhibiting the inflammatory response and the active role of MPO in this cascade (Ai et al, 2013;Liu et al, 2007b). Our findings were in parallel with the others: lung tissue MPO activities of the rats subjected to I/R were significantly higher.…”
Section: Discussionsupporting
confidence: 89%
“…Lung pathology and injury analysis Pulmonary vascular permeability and wet/dry weight ratio were measured as described previously [20] . The left lung was obtained and weighed immediately and 72 h after storage at 60 o C to determine the wet/dry weight ratio of the lung tissue.…”
Section: Oxidation Evaluationmentioning
confidence: 99%
“…Following thermal injury, the small intestine is subjected to ischemia, and consequently, especially during burn resuscitation, reperfusion injury occurs [8] . Intestinal ischemia-reperfusion results in organ injury through both tissue hypoxia and reperfusion phenomena mediated by inflammatory response and oxidative stress [9,10] . There is increasing evidence that the inflammatory response and oxidative stress in the small intestine exert important roles in the bacteria or endotoxin translocation and the development of SIRS after thermal injury [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%